EFEKTIFITAS PROGRAM TAMBAHAN DALAM MENINGKATKAN KEMAMPUAN PENGENALAN MEMBACA PADA ANAK KELOMPOK B DI TK ISLAM PLUS AL MUCHLISIN - Nina Nuriyah Ma’arif; Wahyu Safarina (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2022)
This article aims to examine the effectiveness of the additional class program in improving group B grade students' early reading skills at Islamic Kindergarten Plus Al Muchlisin in Gresik city, as well as its influence factors. Using a descriptive qualitative approach, the findings illustrate that the additional program is quite effective in improving the ability to read in early childhood students. The evidence is that all students (20 children) who are involved in this program are able to